Efficacy and safety of empagliflozin in glycogen storage disease type Ib: data from an international questionnaire - Grünert, Sarah; Derks, Terry G. J.; Adrian, Katarina; Al-Thihli, Khalid; Ballhausen, Diana; Bidiuk, Joanna; Bordugo, Andrea; Boyer, Monica; Bratkovic, Drago; Brunner-Krainz, Michaela; Burlina, Alberto; Chakrapani, Anupam; et al. (Genetics in medicine, 2022)
Purpose - This paper aims to report collective information on safety and efficacy of empagliflozin drug repurposing in individuals with glycogen storage disease type Ib (GSD Ib). - Methods - This is an international retrospective questionnaire study on the safety and efficacy of empagliflozin use for management of neutropenia/neutrophil dysfunction in patients with GSD Ib, conducted among the respective health care providers from 24 countries across the globe. - Results - Clinical data from 112 individuals with GSD Ib were evaluated, representing a total of 94 treatment years. The median age at start of empagliflozin treatment was 10.5 years (range = 0-38 years). Empagliflozin showed positive effects on all neutrophil dysfunction-related symptoms, including oral and urogenital mucosal lesions, recurrent infections, skin abscesses, inflammatory bowel disease, and anemia. Before initiating empagliflozin, most patients with GSD Ib were on G-CSF (94/112; 84%). At the time of the survey, 49 of 89 (55%) patients previously treated with G-CSF had completely stopped G-CSF, and another 15 (17%) were able to reduce the dose. The most common adverse event during empagliflozin treatment was hypoglycemia, occurring in 18% of individuals. - Conclusion - Empagliflozin has a favorable effect on neutropenia/neutrophil dysfunction-related symptoms and safety profile in individuals with GSD Ib.